A mitigação do desperdício de hortifrutícolas nos pequenos e médios centros de abastecimento: estudo de caso no município de Imperatriz - MA - Sales, Francisco Carlos Vaz (Universidade do Vale do Rio dos Sinos, 2023)
Regarding both food security and environmental issues, food waste constitutes a serious global problem that requires concerted action from all stakeholders in the Food Supply Chain (FSC). Losses occur from agricultural producers to consumers, throughout the entire food supply chain. The case is that Fruits and Vegetables (F&V) are sensitive products subject to various adverse factors that pose risks of both microbiological deterioration and mechanical damage throughout the food supply chain. The problem is that the FSC is structured as a complex network polarized by producers, distributors, retailers, and consumers, with distributors, despite being less visible, playing a crucial role in the smooth functioning of this market. In the municipality of Imperatriz - MA, distributors, who have a significant role in both the local and regional economy, have been a scene of considerable food waste attributed to deficiencies in both production and supply, including more complex causes in transportation and distribution. The seriousness of the problem requires studies aimed at assessing the losses and formulating guidelines to mitigate them. Thus, this study proposed the following questions: 1) What causes waste in the distribution of fruits and vegetables? 2) How to mitigate food waste in regional distribution of F&V? The unfolding of this issue aimed to achieve the following objectives: a) investigate qualitative losses (more difficult to determine) and their impact on demand; b) diagnose the main causes of losses; c) evaluate the modus operandi and cost of discarding these losses; d) identify preventive and mitigating procedures adopted and potential innovations. In order to establish a knowledge base for the proposed issue, preliminary information was gathered through a literature review. In a second stage, on-site visits were conducted to apply a questionnaire to a sample of the researched population. The study reveals the precariousness of the horticultural supply chain in Imperatriz - MA. The majority of products come from other states, indicating a near total lack of local participation. It is necessary to create a corresponding supply to meet the demand, streamline the supply chain, improve quality, reduce costs, and make the products accessible to the low-income population. Despite the challenges, implementing remedial measures can encourage the development of the horticultural agribusiness, stimulate the market, and benefit all those involved in the production, distribution, and commercialization of these products in the municipality.
Keywords: Desperdício de alimentos; Causas do desperdício na distribuição; Mitigação do desperdício na distribuição regional; Diretrizes de mitigação; Segurança alimentar; Cadeia de Suprimento Alimentar - CSA; Frutas e Hortaliças - F&H; Perdas na cadeia de suprimentos; Deterioração microbiológica; Food waste; Causes of waste in distribution; Mitigation of waste in regional distribution; Mitigation guidelines; Food security; Food Supply Chain - FSC; Fruits and Vegetables - F&V; Losses in the supply chain; Microbiological deterioration; ACCNPQ::Engenharias::Engenharia de Produção